Wells Reserve Research Library: A Use and User Analysis. - Bevan Angier; Kathleen Spahn; Anne Piergrossi (Issues in Science and Technology Librarianship)
This study focuses on the collection of a small science library within the National Estuarine Research Reserve System. It reviews the history, context, and existing constraints on its collection and development and suggests ways in which the library might overcome barriers in its effort to obtain grants for its expansion of print materials. The library plays a three-fold role in the local community: it hosts both staff and visiting scientists conducting estuarine research; it educates the local community -- schoolchildren, adults, and policymakers; and it advocates for sensitive and sustainable stewardship of the land in partnership with local organizations and policymakers. The Education Director has been repeatedly turned down in her attempts to obtain grant money because the library is too new (to the public) to demonstrate any user base or long-term viability. Granting organizations suggested she come back for reconsideration when rising usage statistics could be demonstrated. This study seeks to propose a method by which the Wells Research Library can measure the use of its collection and more accurately identify its user base and attempts to bring together a variety of tools and methods into a single cohesive measurement process. Once established as a routine, the regular collection of data can be used to demonstrate patterns and changes in the library's use and user base over time, and thereby be able to present such data to granting organizations. This system can be adapted by any small specialized library interested in measuring its users and usage on a regular basis -- particularly one connected to a nonprofit or parent organization. [ABSTRACT FROM AUTHOR]